1.4 nm gold nanoparticle-antibody conjugates for in situ gold immunolabelling after transduction into living human cells - Groysbeck, Nadja; Haeberlé, Anne Marie; Ory, Stéphane; Hanss, Victor; Eltsov, Mikhael; Schultz, Patrick; Zuber, Guy (Comptes Rendus. Chimie, 2023)
Despite advances in Electron Microscopy (EM) that enable to image protein assemblies within vitreous sections of cells at nearly atomic resolution, labelling is still necessary to locate small proteins or rare complexes. Gold immunolabelling has been used for decades to localise specific proteins within cellular sections. However, current gold particle-antibody conjugates are not built with enough chemical precision to match the current resolution offered by cryo-EM methodology. Furthermore, as a close to native specimen state can only be achieved by strict preservation of a frozen hydrated state, it is required to deliver gold labelling agents into living cells prior to their vitrification. Several 1.4 nm gold nanoparticle-antibody conjugates were synthesised. Their abilities to bind to and label their corresponding epitopes within living cells after cytosolic delivery by electroporation are documented here.